Airway management after maxillectomy with free flap reconstruction. Issue 8 (21st August 2012) - Brickman, Daniel S.; Reh, Douglas D.; Schneider, Daniel S.; Bush, Ben; Rosenthal, Eben L.; Wax, Mark K.
Abstract Background Maxillectomy defects require complex 3‐dimensional reconstructions often best suited to microvascular free tissue transfer. Postoperative airway management during this procedure has little discussion in the literature and is often dictated by surgical dogma. The purpose of this article was to review our experience in order to evaluate the effect of airway management on perioperative outcomes in patients undergoing maxillectomy with free flap reconstruction. Methods A retrospective chart review was performed on patients receiving maxillectomy with microvascular reconstruction at 2 institutions between 1999 and 2011. Patient's airways were managed with or without elective tracheotomy at the surgical team's discretion and different perioperative outcomes were measured. The primary outcome was incidence of airway complication including pneumonia and need for further airway intervention. Secondary outcome was measured as factors leading to perioperative performance of the tracheotomy. Results Seventy‐nine of 143 patients received elective tracheotomy perioperatively. The incidence of airway complication was equivalent between groups (10.1% vs 9.4%; p = .89). Patients with cardiopulmonary comorbidities were more likely to receive perioperative tracheotomy (74.1% vs 50.9%; p = .03) without a difference in airway complications. Other patient cofactors did not have an impact on perioperative tracheotomy or airway complication rate. Conclusions Elective tracheotomy may safely be avoided in a subset of patients undergoing maxillectomy with microvascular reconstruction. Elective tracheotomy should be considered in patients with cardiopulmonary risk factors. Head Neck, 2013